Perbandingan Daya Dukung Pondasi Sumuran dengan Pondasi Tiang Pancang pada Tanah Pesisir Berdasarkan Data Standard Penetration Test (SPT) pada Jembatan Gantung Desa Cemara Kecamatan Lembar Kabupaten Lombok Barat - Muhammad Sapdi; Hafiz Hamdani; Ari Ramadhan Hidayat (Jurnal Talenta Sipil, 2026)
Infrastructure development in coastal areas is a strategic challenge in regional planning and civil engineering, due to complex soil characteristics, high sedimentation rates, and the influence of the marine environment that can reduce structural performance, especially in bridge construction. Saturated sandy soil conditions commonly found in coastal areas require the selection of appropriate foundation types to be able to safely support structural loads. This study aims to compare the bearing capacity of pit foundations and pile foundations on coastal soils based on Standard Penetration Test (SPT) data. The research method used is quantitative analysis with a comparative approach using the Meyerhof (1976) and Terzaghi (1943) methods. Secondary data in the form of SPT test results were obtained from the Suspension Bridge construction project in Cemara Village, Lembar District, West Lombok Regency. Calculations include end bearing capacity, cover bearing capacity, ultimate bearing capacity, allowable bearing capacity, and group pile bearing capacity. The analysis results show that pile foundations have a greater group pile bearing capacity than pit foundations. Based on the Meyerhof method (1976), the bearing capacity of the pile foundation group is 20,707.43 kN and the well foundation is 4,161.63 kN. Meanwhile, based on the Terzaghi method (1943), the bearing capacity of the pile foundation is 9,183.07 kN and the well foundation is 3,241.08 kN. These results indicate that pile foundations are more recommended for use in coastal soil conditions with low bearing capacity.